A Study on Wireless Networking Simulation of Train Bogie Sensors - FENG Dong; FENG Ye (Kongzhi Yu Xinxi Jishu)
The status monitoring system of train bogie is key to the overall health monitoring of a train. Typically dozens of sensors, like axle temperature monitoring, instability detection, vibration impact monitoring, etc., are deployed on each bogie, making the overall bogie wiring complex and maintenance challenging. In this paper, the ZigBee wireless communication technology and a cluster-based networking approach are employed to form a wireless sensor network for each bogie system. This significantly reduces the deployment time and cost and makes operation and maintenance more convenient. By utilizing network simulation tool NS2, a train bogie wireless sensor network model based on the IEEE 802.15.4 standard and the Ad Hoc on-demand distance vector (AODV) routing protocol was built. To mitigate packet loss rate and decrease end-to-end communication delay, modifications to the AODV protocol were undertaken based on the route timeout mechanism, the lifecycle of route request (RREQ), and the direction of RREQ propagation. Simulation results illustrate that, following the improvements, the AODV protocol reduces by 32% the time to reestablish communication after interruption. Simultaneously, packet loss rate and end-to-end communication delay are both reduced by over 50%. These results demonstrate that the wireless sensor network design proposed in this paper can satisfy the data transmission requirements of train bogie sensors.